Pengawasan Ombudsman Republik Indonesia terhadap Pelaksanaan Putusan Pengadilan Tata Usaha Negara - Dahlena Dahlena (Lex Renaissance, 2016)
AbstractThis research focuses on two issues: first, the authority of Ombudsman of Indonesia Republic (locally abbreviated as ORI) in monitoring any verdicts of civil service arbitration tribunal and second, the procedure of monitoring of Ombudsman of Indonesia Republic in encouraging the implementation of the verdict of civil service arbitration tribunal. This is a normative research in which its results conclude that: first, the law about the civil service arbitration tribunal explicitly does not mandate the Ombudsman of Indonesia Republic to do a monitoring to the implementation of the verdict of civil service arbitration tribunal but, if seen from the valid law Number 5 of 1986, Law Number 23 of 2014, Law Number 25 of 2009 and Law Number No. 37 of 2008, the Ombudsman of Indonesia Republic has an authority to do the monitoring with three reasons:  i) apparatus is the target of Ombusman monitoring; ii) the action of apparatus in contradict with the legal court verdict seen as arbitrary action as a part of maladministration becomes the authority of Ombudsman of Indonesia Republic; and  iii) the report to the legislative institutions and publication as the external procedures in the implementation of the verdict of civil service arbitration tribunal need to be supported with the participation of society through the complaints reported to Ombudsman of Indonesia Republic that acts as the controller of public service. Second, the monitoring procedure towards the implementation of the verdict of civil service arbitration tribunal is implemented through any demands of clarification, investigation, mediation and recommendation.  Keywords: Monitoring, Ombudsman of Indonesia Republic, verdict of civil service arbitration tribunal